Evaluation of the Early Development of 6-Month-Old Babies in the Case of Maternal Postpartum Depression with or Without Bipolar Disorder - Jokthan Guivarch; Mélanie-Lou Persia; Laure Le Treut; Pauline Grandgeorge; Federico Solla; Hugo Pergeline; Michel Dugnat; Florence Askenazy; François Poinso; Arthur Varoquaux; Arnaud Fernandez (Children)
Background: The first year of life is the period of greatest brain plasticity. Postpartum depression can adversely affect the first interactions with the child and, consequently, their emotional, social, and cognitive development. Objectives: First, to describe the developmental profile of six-month-old infants of mothers suffering from severe postpartum depression, and, second, to compare the development of infants whose mothers suffer from depression with or without bipolar disorder. Methods: This is a retrospective descriptive study on 6-month-old babies hospitalized with their mothers at the Marseille Mother–Baby Unit (MBU) for maternal postpartum depression with or without bipolar disorder. Mothers were clinically diagnosed by a psychiatrist specialized in postpartum depression using the DSM-5; infant development was assessed at 6 months by an independent health professional using the revised Brunet–Lézine Scale, which allowed the calculation of global and partial developmental quotients (DQ). Results: We followed 40 mother–infant dyads. None of the 40 infants had a global developmental delay. However, maternal depression was significantly associated with poorer sociability (mean sociability DQ score of 94 ± 9.6, p < 0.001) and lower postural development (mean postural DQ score of 96.2 ± 8.9 *, p < 0.001) in the infants at 6 months of age. Postural development was significantly lower in children of bipolar mothers than in children of non-bipolar mothers (p = 0.03). Conclusions: Postpartum depression was associated with a weakness in sociability and posture at the age of 6 months, without relevant developmental delay. Screening infants at an early age with specific tools allows for earlier intervention, which would positively influence their developmental trajectory.